A systematic review of the phytochemical profile and medicinal significance of Evolvulus alsinoides - Cheekavolu C; Karnam N; Choudhary N; Sangeeta BSR; Mavillapalli RC (Journal of Medical and Scientific Research)
Background: The perennial herb Evolvulus alsinoides L., sometimes called "Vishnukranthi" or "Shankhpushpi," belongs to the Convolvulaceae family. Traditional medicine utilises the entire plant and its various parts to treat multiple ailments, including stomach ulcers. This review aimed to analyse the phytochemical constituents of extracts of E. alsinoides and highlights its medicinal importance.